(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2019)
The blast in personal digital technologies worldwide, including Indonesia, offers rising opportunities to create digital media. Along with digital media creation for education, both creativity and conceptual understanding must be involved. Therefore, this research is aimed to investigate the influence of Slowmation (Student-created Slow Motion Animation) on students’ creativity and knowledge of heat transfer. The study used a pre-experimental: one group pretest-post-test design. The sample was taken by convenience sampling technique in experimental class (n=20) with the population of 8th-grade students at independence secondary school in Bandung. Students’ understanding result was obtained through the objective test with the development of a normalized gain of 0.30 (0.70 > <g> ≥ 0.30) as medium improvement, while students’ creativity gained through the creative process and product of Slowmation with 78.2 as an above standard category. ABSTRAK Perkembangan personal teknologi digital di seluruh dunia, termasuk Indonesia, menawarkan peluang yang meningkat untuk menciptakan media digital. Seiring dengan penciptaan media digital untuk pendidikan, secara bersamaan, kreativitas dan pemahaman konseptual harus dilibatkan. Oleh karena itu, penelitian ini bertujuan untuk mengetahuipengaruh Slowmation (Animasi Gerakan Lambat Buatan Siswa) terhadap kreativitas dan pengetahuan siswa tentang perpindahan panas. Penelitian ini menggunakan pre-experimental: one group pretest-post-test design. Pengambilan sampel dilakukan dengan teknik convenience sampling pada kelas eksperimen (n=20) dengan populasi siswa kelas VIII SMAN Mandiri Bandung. Hasil pemahaman siswa diperoleh melalui tes objektif dengan pengembangan gain ternormalisasi sebesar 0,30 (0,70 > <g> 0,30) sebagai peningkatan sedang, sedangkan kreativitas siswa diperoleh melalui proses kreatif dan produk Slowmation dengan 78,2 seperti di atas kategori standar.